Strategi Pembelajaran Pendidikan Islam Melalui Pendekatan Storytelling untuk Membentuk Akhlak Mulia Anak Usia Dini - Hanifah Muthia Nabihasnah; Marsya Alhayyu; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the application of storytelling in Islamic education as a method to cultivate noble character in early childhood. Storytelling is an effective approach to convey moral values and Islamic ethics through stories that touch children's emotions and imagination. The research method used is a literature review, which involves collecting, analyzing, and studying various literature related to Islamic education, children's character, and the application of storytelling in the context of religious education. The findings indicate that storytelling not only helps children understand moral values but also enhances empathy, religious awareness, and the formation of positive habits that are sustainable. This study also emphasizes the importance of the role of teachers and the environment in supporting the internalization of moral values in children. Overall, storytelling can be an effective method in early childhood moral education, with significant contributions to the formation of Islamic character.